Requirements engineering for sociotechnical systems - Maté, José Luis; Silva, Andrés (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
"This book provides a detailed account concerning information society and the challenges and application posed by its elicitation, specification, validation and management: from embedded software in cars to internet-based applications, COTS packages, health-care, and others"--Provided by publisher.